ANALISIS KRITIS TERHADAP BUNGA BANK - H. Syahrul, H. Syahrul (DIKTUM: Jurnal Syariah dan Hukum, 2014)
This article describes the Banks interest-critical analysis problems. From the discussion, it is understood that the interest in terms of conventional economics is the remuneration given by the bank based on the conventional principle to customers who purchase or sell products. In the classical view, the conventional economic Nakar interest rates and savings related to each other, therefore the interest rate is the most important factor, which regulates the volume of savings. The higher the interest rate, increasingly also reward saving. Thus, the higher the propensity to save or otherwise, therefore it can be understood that in the interest of conventional banks is the spirit in promoting economic income Han banking business. In view of the interest of Islamic economics is additional (ziada) and in this context, Islam considers that interest is riba therefore unlawful bank interest and it can no longer be denied because it is in accordance with what is in the Quran and Sunnah about Riba is synonymous with the concept of interest. Bank interest in relation to Islamic economics can impede the economic and equitable distribution of income and can even lead to financial crisis / financial. Thus the interest-free Islamic banking system actually provides assurance or certainty in the economy interact. Because Islamic banks can ensure avoiding of brutality and economic injustice.